Analisis Kondisi Sosial Ekonomi Petani Karet di Kecamatan Karang Baru Kabupaten Aceh Tamiang - Loren Sahara (Fakultas Ekonomi Universitas Samudra, 2022)
This study aims to determine the analysis of the factors that affect the production of fishermen in Kuala Langsa, West Langsa District, Langsa City. This research was carried out from January 2021 to July 2021. The sources of data collected in the form of primary were obtained through observation, interviews and questionnaires, and secondary data obtained from the Department of Food, Agriculture, Maritime Affairs and Fisheries and the Village Office. The sample of this research is as many as 66 respondents by using data analysis method Purposive Sampling. This research model uses multiple linear analysis using the E-views version 11. The results of the study with a significant level of 5% show that the variable Y = -10,79747 + 4.24X1 + 4.090560X2 + 5.703930X3 + 0.781140X4, from the t-test it can be explained that capital has a positive and significant effect on fishermen's production where the probability value is 0.0005 <0.05. Labor has a positive and significant effect on fishermen's production where the probability value is 0.0016 <0.05. The length of time at sea has a positive and significant effect on fishermen's production where the probability value is 0.0021 <0.05. The size of the fishing area has a positive and significant effect on the production of fishermen where the probability value is 0.0172 <0.05. From the results of the F test, it can be explained that capital (X1), labor (X2), length of time at sea (X3), and wide fishing area (X4) simultaneously have a positive and significant effect on fishermen's production where the probability is 0.000000 < 0 ,05. From the results of the analysis of the coefficient of determination, it can be explained that capital, labor, length of time at sea, and the size of the fishing area affect the production of fishermen in Kuala Langsa by 84.91%, while the remaining 15.91%. This is influenced by other factors outside of this study.